Preparation method of solid lithium hexafluorophosphate crystal
By using a continuous reaction crystallization process in the preparation of lithium hexafluorophosphate, the key parameter correlation value α is controlled, and the problems of cumbersome preparation process, low efficiency and uneven particle size in the existing technology are solved, and efficient and low energy consumption of lithium hexafluorophosphate crystal preparation is achieved. The product has uniform particle size, high purity, and significantly improved production efficiency.
Patent Information
- Application Number
- CN202411944410.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The existing preparation methods for lithium hexafluorophosphate have problems such as cumbersome processes, many equipment, high investment, poor operation stability, low production efficiency, low product yield and high energy consumption, and it is difficult to effectively control particle size uniformity and avoid impurity double-clustering.
The continuous reaction crystallization process is adopted to prepare lithium hexafluorophosphate crystals by directly reacting and crystallizing the correlation value α of the key parameters within the range of 3 to 5, achieving particle size uniformity and efficient production.
The crystallization efficiency is improved, energy consumption is reduced, and lithium hexafluorophosphate crystals with uniform particle size and high purity are obtained, and the production time is shortened and the production efficiency is improved. The crystallization yield after mother liquor reuse can reach more than 99%.
Smart Images

Figure CN119797397A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparing lithium hexafluorophosphate, and in particular to a method for efficiently preparing lithium hexafluorophosphate crystals with uniform particle size. Background Art
[0002] Lithium hexafluorophosphate is an important component of the electrolyte. Due to its high solubility, good antioxidant capacity and strong electrochemical stability, it is considered to be the best lithium battery electrolyte with comprehensive performance. Lithium hexafluorophosphate accounts for about 20% of the total mass of the electrolyte and 80% of the total cost of the electrolyte. Therefore, the manufacturing cost of lithium hexafluorophosphate directly affects the market price of lithium batteries.
[0003] LiF+PF5→LiPF6
[0004] At present, the mainstream production route of lithium hexafluorophosphate is the cooling crystallization method using HF as a solvent. First, gaseous phosphorus pentafluoride reacts with lithium fluoride dissolved in anhydrous hydrogen fluoride solution to produce a lithium hexafluorophosphate solution, which is then frozen and crystallized to precipitate lithium hexafluorophosphate.
[0005] However, this method still has the following problems: ① The industry adopts intermittent crystallization process, which has complicated procedures, a large number of equipment and high investment costs; ② The operation is unstable, the cooling crystallization time is long, the production efficiency is low, the single-pass yield of the product is low, and the mother liquor is repeatedly heated and cooled during recycling, resulting in high energy consumption.
[0006] Patent CN117797743A discloses a continuous production method for hexafluorophosphate, namely, producing products with uniform particle size by reaction crystallization coupling. However, this method does not mention the key control rules of reaction crystallization operation parameters, and crystal particles with uniform particle size are only obtained by screening the crystal particles in a special reactor form. The problem of large particles clogging pipelines, which is common in the industry, still cannot be effectively solved.
[0007] Patent CN114695952A reports a method for producing lithium hexafluorophosphate by a dynamic constant temperature crystallization method, which can effectively shorten the induction period of crystal generation and accelerate the crystallization rate. At the same time, the particle size range of the product is small, and the obtained lithium hexafluorometaphosphate product has high purity and uniform particle size. However, the method uses an overly high concentration of lithium fluoride solution, which can easily lead to the inclusion of lithium fluoride in the crystal, resulting in unqualified products. In addition, the particle size of the crystals prepared by this method is mostly above 500μm, and the acidity of the crystals is difficult to guarantee. In addition, this method still does not propose an effective method for parameter control of reactive crystallization.
[0008] Therefore, in order to solve the above problems, it is necessary to develop a method for efficiently preparing lithium hexafluorophosphate crystals, shorten the time required for cooling crystallization, reduce production energy consumption, improve production efficiency, and make the crystal particle size uniform to avoid inclusion of impurity components. Summary of the invention
[0009] In order to solve the above technical problems, the present invention proposes a method for preparing solid lithium hexafluorophosphate crystals. The present invention adopts a continuous reaction crystallization process and controls the correlation value α of key parameters affecting the crystallization process within a certain range, and directly reacts and crystallizes to quickly obtain lithium hexafluorophosphate crystal particles with uniform particle size, which has the advantages of high crystallization efficiency, low energy consumption and high product quality.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing solid lithium hexafluorophosphate crystals comprises the following steps:
[0012] 1) continuously introducing PF5 gas into a reaction crystallizer to react with a hydrogen fluoride solution of LiF and directly crystallize to prepare lithium hexafluorophosphate crystals, and maintaining the reaction system at normal pressure during the reaction;
[0013] 2) A slurry containing lithium hexafluorophosphate is obtained at the reactor outlet, and lithium hexafluorophosphate crystals are obtained after conventional filtration and drying.
[0014] 3) The characteristic value α during the reaction is controlled to be 3 to 5, preferably 3.5 to 4.5.
[0015] α=[(R*r / 100c)^2 / T]*F+t
[0016] Wherein, R is the ratio of the diameter of the stirring paddle of the reactor to the inner diameter of the reactor, r is the stirring rate, the unit is Rpm, c is the mass concentration of lithium fluoride in the hydrogen fluoride solution of lithium fluoride, T is the reaction crystallization temperature, the unit is K, F is the flow rate of the hydrogen fluoride solution of LiF, the unit is kg / min, and t is the residence time of the reaction crystallization, the unit is h.
[0017] In a preferred embodiment, in step 1), the feed ratio of PF5 to LiF is 1.00-1.10, preferably 1.03-1.05:1 in terms of molar ratio;
[0018] Preferably, in the hydrogen fluoride solution of LiF, the mass concentration of LiF is 6.0-8.0%, preferably 6.5-7.0%.
[0019] Preferably, the LiF hydrogen fluoride solution is an anhydrous LiF hydrogen fluoride solution.
[0020] In a preferred embodiment, in step 1), the feed flow rate of the hydrogen fluoride solution of lithium fluoride is controlled at 0.3-1.0 kg / min, preferably 0.6-0.8 kg / min;
[0021] Preferably, the reaction crystallization temperature is 273.15-291.15K, preferably 283.15-288.15K;
[0022] Preferably, the reaction residence time is 1.0-3.0h, preferably 1.2-2.0h;
[0023] Preferably, in the reaction crystallizer, the stirring speed r is 200-500 Rpm, preferably 300-400 Rpm;
[0024] In a preferred embodiment, in step 1), the ratio R of the diameter of the stirring paddle of the reactor to the inner diameter of the reactor is 0.5 to 0.9, preferably 0.7 to 0.8.
[0025] The particle size distribution D50 of lithium hexafluorophosphate crystals prepared by the method of the present invention is between 140-160 μm, 90% of the crystal particle size is distributed between 100-300 μm, and the particle size uniformity is good. The present invention adopts a reaction + crystallization coupling process, and by associating relevant reaction parameters and defining an α value, it is used to accurately control the crystallization conditions, adjust the supersaturation of the reaction crystallization, and prepare product crystals with high purity and uniform particle size.
[0026] The lithium hexafluorophosphate crystals prepared by the method of the present invention have good uniformity of particle size, high product purity, and impurities such as HF, H2O and metal ions meet product specifications; and through reaction crystallization coupling, the production time is significantly shortened and the production efficiency is improved; after the crystallization mother liquor of the present invention is reused, the total crystallization yield can reach more than 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a morphology picture of the lithium hexafluorophosphate crystal prepared in Example 1.
[0028] Figure 2 This is a morphology picture of lithium hexafluorophosphate crystals prepared in Comparative Example 1.
[0029] Figure 3 This is a morphology picture of the lithium hexafluorophosphate crystal prepared in Comparative Example 2.
[0030] Figure 4 This is a morphology picture of lithium hexafluorophosphate crystals prepared in Comparative Example 3.
[0031] Figure 5 This is a morphology picture of lithium hexafluorophosphate crystals prepared in Comparative Example 4. DETAILED DESCRIPTION
[0032] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0033] The raw materials used in the examples are all conventional raw materials in the art, and the purity specifications used are analytically pure or chemically pure;
[0034] 1. Information on the source of raw materials in the following examples:
[0035] Phosphorus pentafluoride (99.97%) was purchased from Tianjin Saimet Company, anhydrous hydrogen fluoride was purchased from Zibo Feixiang Chemical, and battery-grade lithium fluoride was purchased from Taixing Yinxin Chemical Technology Co., Ltd.
[0036] 2. The test methods used in each example of the present invention:
[0037] Acidity analysis of lithium hexafluorophosphate crystal product: Using bromothymol blue as an indicator, 0.01 mol / L sodium hydroxide standard solution is used to titrate the free acid (in terms of HF) in 0.1 g / mL lithium hexafluorophosphate crystal sample. The calculation formula is:
[0038] w=(V-V0)cM / (m×10 -3 )
[0039] Where:
[0040] V—the sodium hydroxide standard titration solution consumed by titrating the test solution, in ml;
[0041] V0—the amount of sodium hydroxide standard solution consumed in titrating the blank test solution, in ml;
[0042] c—The accurate concentration of sodium hydroxide standard solution, in mol / L;
[0043] m—the mass of solid in the sample, in g;
[0044] M—molar mass of hydrogen fluoride, in g / mol
[0045] The moisture content was determined using a Lesder LSDKS-RLJ2 automatic fast Karl Fischer moisture analyzer with a test range of 1ppm-100% water, measuring voltage: constant current polarization detection, and electrolysis current: automatic pulse current 400mA.
[0046] The metal ions were determined using the ICAP7200 inductively coupled plasma optical emission spectrometer (ICP-OES) from Thermo Fisher Scientific, USA, and the test was carried out according to the standard GB-T19282-2014 method. The content of the corresponding cations (Fe / K / Na / Ni / Zn / Cu, etc.) was measured by comparing the standard concentration curve of each cation.
[0047] The purity analysis of lithium hexafluorophosphate was performed using an American DIONEX ICS-1500 ion chromatograph, AG14 anion protection column, AS14 anion separation column, ULTRA II anion automatic regeneration suppressor, and DS6 heated conductivity cell. The eluent was a mixed solution of 3.5mmol / L Na2CO3 and 1.0mmol / L NaHCO3, the eluent flow rate was 1.2mL / min, the column temperature was 30℃, and the conductivity cell temperature was 30℃.
[0048] The crystal size statistics and photography of lithium hexafluorophosphate were carried out using an Olympus CX41 microscope.
[0049] [Example 1]
[0050] Weigh 35 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 465 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare a 7 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0051] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.03:1 for reaction, wherein the ratio of the reactor stirring paddle diameter to the reactor inner diameter was 0.7, the lithium fluoride solution feed rate was controlled to be 0.7kg / min, the phosphorus pentafluoride feed rate was controlled to be 0.24kg / min, the reaction temperature was controlled to be 283.15K, the reactor liquid level was controlled to be 60%, the reaction residence time was 1.43h, the reactor speed was 330rpm, and the associated parameter α value was 4.12 at this time. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50°C for 2h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0052] The product yield in this example is calculated to be 99.8%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is shown in Figure 1 As shown, the crystal particle size is relatively uniform, the dispersion is good, the crystal morphology is well maintained, and there is no obvious breakage and wear.
[0053] [Example 2]
[0054] Weigh 30 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 470 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare a 6 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0055] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.01:1 for reaction, wherein the ratio of the reactor stirring paddle diameter to the reactor inner diameter was 0.9, the lithium fluoride solution feed rate was controlled to be 1.0 kg / min, the phosphorus pentafluoride feed rate was controlled to be 0.29 kg / min, the reaction temperature was controlled to be 284.15 K, the reactor liquid level was controlled to be 60%, the reaction residence time was 1.0 h, the reactor speed was 220 rpm, and the correlation parameter α value was 4.83 at this time. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50° C. for 2 h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0056] The product yield in this example is calculated to be 99.3%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is shown in Figure 1 As shown, the crystal particles are basically spherical, and the size is relatively uniform and the dispersion is good.
[0057] [Example 3]
[0058] Weigh 40 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 460 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare 8 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0059] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.08:1 for reaction, wherein the ratio of the reactor stirring paddle diameter to the reactor inner diameter was 0.6, during the reaction, the lithium fluoride solution feed rate was controlled to be 0.36kg / min, the phosphorus pentafluoride feed rate was 0.15kg / min, the reaction temperature was controlled to be 288.15K, the reactor liquid level was controlled to be 60%, the reaction residence time was 2.78h, the reactor speed was 380rpm, and the associated parameter α value was 3.79 at this time. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50°C for 2h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0060] The product yield in this example is calculated to be 99.5%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is shown in Figure 1 As shown, the crystal particles are basically spherical, and the size is relatively uniform and the dispersion is good.
[0061] [Example 4]
[0062] Weigh 32.5 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 467.5 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare a 6.5 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0063] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.05:1 for reaction, wherein the ratio of the reactor stirring paddle diameter to the reactor inner diameter was 0.5, the lithium fluoride solution feed rate was controlled to be 0.83kg / min, the phosphorus pentafluoride feed rate was 0.27kg / min, the reaction temperature was controlled to be 273.15K, the reactor liquid level was controlled to be 60%, the reaction residence time was 1.20h, the reactor speed was 320rpm, and the associated parameter α value was 3.01 at this time. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50°C for 2h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0064] The product yield in this example is calculated to be 99.2%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is shown in Figure 1 As shown, the crystal particles are basically spherical, and the size is relatively uniform and the dispersion is good.
[0065] [Example 5]
[0066] Weigh 37.5 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 462.5 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare a 7.5 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0067] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.10:1 for reaction, wherein the ratio of the diameter of the reactor stirring paddle to the inner diameter of the reactor was 0.5, the lithium fluoride solution feed rate was controlled to be 0.59kg / min, the phosphorus pentafluoride feed rate was 0.24kg / min, the reaction temperature was controlled to be 291.15K, the reactor liquid level was controlled to be 60%, the reaction residence time was 1.69h, the reactor speed was 480rpm, and the correlation parameter α value was 3.77 at this time. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50°C for 2h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0068] The product yield in this example is calculated to be 99.7%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is shown in Figure 1 As shown, the crystal particles are basically spherical, and the size is relatively uniform and the dispersion is good.
[0069] [Comparative Example 1]
[0070] Lithium hexafluorophosphate crystals were prepared in a method substantially the same as in Example 1, except that the stirring speed was adjusted to 450 rpm, and the α value obtained was 6.4.
[0071] The single-pass yield of the product in this comparative example is calculated to be 98.8%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is as follows: Figure 2 As shown, the crystals are severely broken and the particle size distribution becomes broad.
[0072] [Comparative Example 2]
[0073] Lithium hexafluorophosphate crystals were prepared in a method substantially the same as in Example 1, except that the mass concentration of lithium fluoride was 10%, and the α value obtained was 2.7.
[0074] The single-pass yield of the product in this comparative example is calculated to be 99.1%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is as follows: Figure 3 As shown, there is a certain amount of aggregation of the crystal particles.
[0075] [Comparative Example 3]
[0076] The reaction crystallization of lithium hexafluorophosphate was carried out according to the method in Example 1 of patent CN117923527B.
[0077] Weigh 45 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 455 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare a 9.0 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0078] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.05:1 for reaction, wherein the ratio of the reactor stirring paddle diameter to the reactor inner diameter was 0.45 (the CN117923527B patent was not disclosed in detail, according to the conventional reactor regulations), the lithium fluoride solution feed rate was controlled to be 0.67kg / min, the phosphorus pentafluoride feed rate was 0.31kg / min, the reaction temperature was controlled to be 278.15K, the reactor liquid level was controlled to be 60%, the reaction residence time was 1.5h, the reactor speed was 300rpm, and the associated parameter α value was 2.03. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50°C for 2h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0079] The single-pass yield of the product in this comparative example is calculated to be 99.0%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is as follows: Figure 4 As shown, the crystal sizes are different and there is serious crystal agglomeration, which easily leads to serious inclusion of impurities.
[0080] [Comparative Example 4]
[0081] The reaction crystallization of lithium hexafluorophosphate was carried out according to the method in Example 1 of patent CN114695952B.
[0082] Weigh 60 kg of battery-grade lithium fluoride into a 500 L raw material kettle, add 440 kg of anhydrous hydrofluoric acid, stir to dissolve, and prepare a 12.0 wt % lithium fluoride anhydrous hydrogen fluoride solution in advance.
[0083] Lithium fluoride and phosphorus pentafluoride were pumped into a 100L reactor at a molar ratio of 1.05:1 for reaction, wherein the ratio of the reactor stirring paddle diameter to the reactor inner diameter was 0.45 (the CN114695952B patent was not disclosed in detail, according to the conventional reactor regulations), the lithium fluoride solution feed rate was controlled to be 0.10kg / min, the phosphorus pentafluoride feed rate was 0.06kg / min, the reaction temperature was controlled to be 273.15K, the reactor liquid level was controlled to be 60%, the reaction residence time was 10h, the reactor speed was 300rpm, and the associated parameter α value was 10.05. The slurry obtained by the reaction was filtered to obtain lithium hexafluorophosphate crystals, the mother liquor was reused, and the product crystals were dried at 50°C for 2h under a nitrogen atmosphere to obtain lithium hexafluorophosphate products.
[0084] The single-pass yield of the product in this comparative example is calculated to be 98.9%. The analysis results of lithium hexafluorophosphate crystals are shown in Table 1. The crystal morphology is as follows: Figure 5 As shown, the crystal size grows too large, which easily leads to impurity inclusion, and some crystals originate from small crystals that first aggregate and then grow into large crystals.
[0085] Table 1. Analysis of lithium hexafluorophosphate crystals
[0086]
[0087]
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing solid lithium hexafluorophosphate crystals, characterized in that: The following steps are involved: 1) continuously introducing PF5 gas into a reaction crystallizer to react with a hydrogen fluoride solution of LiF and directly crystallize to prepare lithium hexafluorophosphate crystals, and maintaining the reaction system at normal pressure during the reaction; 2) obtaining a slurry containing lithium hexafluorophosphate at the reactor outlet, and obtaining lithium hexafluorophosphate crystals after conventional filtration and drying; 3) wherein the characteristic value α during the reaction is controlled to be 3 to 5, preferably 3.5 to 4.5; α=[(R*r / 100c)^2 / T]*F+t Wherein, R is the ratio of the diameter of the stirring paddle of the reactor to the inner diameter of the reactor, r is the stirring speed, unit is Rpm, c is the mass concentration of lithium fluoride in the hydrogen fluoride solution of lithium fluoride, T is the reaction crystallization temperature, unit is K, F is the flow rate of the hydrogen fluoride solution of LiF, unit is kg / min, and t is the residence time of the reaction crystallization, unit is h.
2. The preparation method according to claim 1, characterized in that: In step 1), the feed ratio of PF5 to LiF is 1.00-1.10, preferably 1.03-1.05:1, in terms of molar ratio; Preferably, in the hydrogen fluoride solution of LiF, the mass concentration of LiF is 6.0-8.0%, preferably 6.5-7.0%; Preferably, the LiF hydrogen fluoride solution is an anhydrous LiF hydrogen fluoride solution.
3. The preparation method according to claim 1, characterized in that: In step 1), the feed flow rate of the hydrogen fluoride solution of lithium fluoride is controlled at 0.3-1.0 kg / min, preferably 0.6-0.8 kg / min; Preferably, the reaction crystallization temperature is 273.15-291.15K, preferably 283.15-288.15K; Preferably, the reaction residence time is 1.0-3.0h, preferably 1.2-2.0h; Preferably, in the reaction crystallizer, the stirring speed r is 200-500 Rpm, preferably 300-400 Rpm; Preferably, in step 1), the ratio R of the diameter of the stirring paddle of the reactor to the inner diameter of the reactor is 0.5 to 0.9, preferably 0.7 to 0.8.
Citation Information
Patent Citations
A system and method for producing lithium hexafluorophosphate by dynamic isothermal crystallization
CN114695952B
A method for preparing alkali metal hexafluorophosphate
CN117923527B